The codex T. III. 2: introductory study and facsimile edition - Ziino, Agostino (Lucca Libreria Musicale Italiana, 1994)
Deluxe edition in full color. Major new source (c.1410-1420) for the works of Antonio Zacara da Teramo and his contemporaries. The repertory mainly consists of settings of the ordinary along with some songs. This newly discovered codex, made up of 15 bifolios, was found as binding material. The ms contains 43 compositions, 23 of which seem to be unica. Full scholarly introduction in It-Eng, accompanied by inventory, watermark evidence, poetic texts, & bibliography.